A novel tissue separation method for determining upper trunk center of gravity in patients with thoracolumbar kyphosis using MIMICS. (January 2020) - Yan, Meijun; Zhang, Yan; Bocobo, Geoffrey A.; Su, Qihang; Zhu, Kai; Zhang, Qiang; Tan, Jun
Abstract: Background: In the past, a variety of methods have been explored to determine the center of gravity or gravity line, such as the hanging method or force plate analysis. However, these methods possess limitations related to precise location of center of gravity. The aim of this study was to describe a tissue separation method to precisely calculate the center of gravity in upper trunk. Methods: Twenty post-operative patients with thoracolumbar kyphosis were retrospectively studied. Center of gravity models were computed: T1–T5 segment, T6–T10 segment and T1–T10 segment. The tissue separation method was used to calculate the center of gravity in each segment. A new center of gravity was composited from T1–T5 segment and T6–T10 segment by composition formula. Similarity and collinearity between center of gravity models was analyzed to verify the reliability of tissue separation method. Correlation between gravity line and theoretic hip axis was compared on pre- and post-operative radiographs to explore their potential application for surgical plan. Findings: Composited center of gravity had significant correlation and high similarity with center of gravity in T1–T10 segment. There was high collinearity between center of gravity points. The post-operative included angle between the gravity line and theoretic hip axis significantly decreased to nearly 0°. Interpretation: These findings demonstrate the MIMICS can reliably calculate the center of gravity in the upper trunk by a tissue separation method. The pre-operative included angle between the gravity line and theoretic hip axis was suggested as a parameter to improve surgical design for thoracolumbar kyphosis correction. Highlights: The gravity line should be considered as a composited result from many center of gravity points. The center of gravity in the upper trunk can be reliably calculated by the tissue separation method. Angle between the gravity line and theoretic hip axis may help thoracolumbar kyphosis correction.